Sprint acceleration mechanics - Morin, J.-B.; Willwacher, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Sprint acceleration is a key feature in many sports performance. It is a direct determinant of performance and the focus of specific training in track and field events such as the 100- or 200-m, but is also paramount in other sports such as soccer or rugby. In the latter, the acceleration capability is a major physical determinant of performance, especially in decisive offensive and defensive actions. In addition, although the exact moment of occurrence is still debated, sprinting and the acceleration phase in particular are the most frequent tasks involved in hamstring strain injuries. Therefore, a better understanding of the mechanical determinants of sprint acceleration performance could help sport practitioners better design training programs, and likely better manage the complex muscle injury prevention / rehabilitation process. However, due to the very fast motion of the human body induced by maximal acceleration (running speeds of more than 10 m.s-1 are reached within a few seconds), and the necessary field (i.e. specific) measurements, valid scientific methods that provide direct, accurate and specific mechanical data over the course of an entire sprint (start + acceleration phases) are scarce.